East meets West: Meditation in distance learning environments - Kristi Archuleta Frush; Kalpana Gupta (Adult Education Research Conference, 2014)
This study investigates the infusion of eastern philosophy, specifically meditation into distance learning environments. How does adding meditative practice alter the learning setting for adult learners in distance learning environments? Literature on learning, yoga, meditation, compressed video, online learning, and neuroscience will be reviewed and addressed to look at the values of practice.